Biología de Valeriana pilosa R. &. P. (Valerianaceae): Una especie en peligro de extinción de las altas montañas de Perú. - Seminario, J.F. (2016)
The study was conducted in an area of natural vegetation in Campo Alegre (3708 m), Huanico, Namora district, Cajamarca (Perú), where Valeriana pilosa R. & P. (“valeriana”) grows spontaneously. Plant, seed, natural regeneration, phenology of populations, leaf area and dry matter allocation of the organs of adult bush were described. Germination tests were performed and the growth of seedlings was evaluated. The plant lives in the scrubland, mainly associated with species of Calamagrostis and Stipa. It is regenerated by seed, under the protection of companion plants. The phenology of populations was related to temperature and rainfall. The leaf area per plant was 925 cm2 and the average harvest index of 35.8%. Thousand seeds weighed 0.2 g and had 43% germination. Seedlings were grown 5.6 mm month-1.